Constructing a Film Character Through Dramaturgical Devices - Ostaszewski, Jacek (Media - Culture - Social Communication, 2021)
The author discusses the process of constructing film characters and equipping them with psychological motivations through dramaturgical means. The first formal device is introducing two narrative lines to the story in which the hero is involved. Adding a second narrative line, based on the protagonist’s emotions, to the main, action-based line, deepens the psychology of the character. The second device is adding a backstory in which the protagonist experiences trauma. This wound from the past motivates the character to act in the main thread, which often makes it possible to work through the trauma from the backstory. Thanks to these measures, the character is more complex, and his or her motivations in the main story gain a realistic justification, and the solution to a problem from the past, i.e. from the backstory, gives a sense of achieving the character’s goals and the completeness of the plot.